Breastfeeding and migraine drugs. - Davanzo, Riccardo; Bua, Jenny; Paloni, Giulia; Facchina, Giulia (Eur J Clin Pharmacol, 2014)
PURPOSE: Breastfeeding women may suffer from migraine. While we have many drugs for its treatment and prophylaxis, the majority are poorly studied in breastfeeding women. We conducted a review of the most common anti-migraine drugs (AMDs) and we determined their lactation risk. METHODS: For each AMD, we collected all retrievable data from Hale's Medications and Mother Milk (2012), from the LactMed database (2014) of the National Library of Medicine, and from a MedLine Search of relevant studies published in the last 10 years. RESULTS: According to our review, AMDs safe during breastfeeding are as follows: low-dose acetylsalicylic acid (ASA), ibuprofen, sumatriptan, metoprolol, propranolol, verapamil, amitriptyline, escitalopram, paroxetine, sertraline, acetaminophen, caffeine, and metoclopramide. AMDs compatible with breastfeeding but warranting caution are as follows: diclofenac, ketoprofen, naproxen, most new triptans, topiramate, valproate, venlafaxine, and cyproheptadine. Finally, high-dose ASA, atenolol, nadolol, cinnarizine, flunarizine, ergotamine, methysergide, and pizotifen are contraindicated. CONCLUSIONS: According to our review, the majority of the revised AMDs were assessed to be compatible with breastfeeding.
Keywords: Adrenergic beta-Antagonists; Analgesics, Non-Narcotic; Animals; Anti-Inflammatory Agents, Non-Steroidal; Anticonvulsants; Antidepressive Agents; Breast Feeding; Calcium Channel Blockers; Female; Humans; Migraine Disorders; Tryptamines